2014
DOI: 10.1111/jasp.12243
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the power of the picture: the effect of image content on emotional and political responses to terrorism

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 54 publications
7
79
0
Order By: Relevance
“…Appraised salience of the stimulus was measured using one measure (“ The image/article was attention‐grabbing ”; 1 = not at all , 7 = strongly ). Finally, participants indicated the extent to which they felt various emotions while viewing the stimulus (1 = not at all , 7 = extremely ), using the same measures as Iyer et al (). Three items assessed fear ( afraid , anxious , frightened ; α = .88), three items measured sympathy ( sympathetic , compassionate , empathetic ; α = .90), and three items assessed anger ( angry , outraged , furious ; α = .91).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Appraised salience of the stimulus was measured using one measure (“ The image/article was attention‐grabbing ”; 1 = not at all , 7 = strongly ). Finally, participants indicated the extent to which they felt various emotions while viewing the stimulus (1 = not at all , 7 = extremely ), using the same measures as Iyer et al (). Three items assessed fear ( afraid , anxious , frightened ; α = .88), three items measured sympathy ( sympathetic , compassionate , empathetic ; α = .90), and three items assessed anger ( angry , outraged , furious ; α = .91).…”
Section: Methodsmentioning
confidence: 99%
“…Although a large body of nonvisual research has shown that emotions can shape individuals' political behavior (e.g., Neuman, Marcus, Crigler, & Mackuen, ), few studies have assessed the contribution of affective responses to visuals in the framing process (Brantner, Lobinger, & Wetzstein, ; Iyer et al, ; Pfau et al, ). This is particularly surprising given that visuals play a leading role compared with text in triggering an emotional response (Iyer & Oldmeadow, ).…”
Section: The Power Of Visualsmentioning
confidence: 99%
See 3 more Smart Citations